A combined ligand- and structure-based approach for the identification of rilmenidine-derived compounds which synergize the antitumor effects of doxorubicin. Issue 14 (15th July 2016) - Vucicevic, Jelica; Srdic-Rajic, Tatjana; Pieroni, Marco; Laurila, Jonne M.M.; Perovic, Vladimir; Tassini, Sabrina; Azzali, Elisa; Costantino, Gabriele; Glisic, Sanja; Agbaba, Danica; Scheinin, Mika; Nikolic, Katarina; et al.
Graphical abstract: Highlights: Identification of rilmenidine-derived compounds with antitumor activity. Combined VS singled out 11 candidates that were synthesized and in vitro tested. Examined compounds haven't shown any significant activity on α2A -adrenoceptors. The most active compound5 exhibited a cytotoxic profile similar to rilmenidine. Compound5 combined with doxorubicin demonstrated synergism in evoking apoptosis. Abstract: The clonidine-like central antihypertensive agent rilmenidine, which has high affinity for I1 -type imidazoline receptors (I1 -IR) was recently found to have cytotoxic effects on cultured cancer cell lines. However, due to its pharmacological effects resulting also from α2 -adrenoceptor activation, rilmenidine cannot be considered a suitable anticancer drug candidate. Here, we report the identification of novel rilmenidine-derived compounds with anticancer potential and devoid of α2 -adrenoceptor effects by means of ligand- and structure-based drug design approaches. Starting from a large virtual library, eleven compounds were selected, synthesized and submitted to biological evaluation. The most active compound5 exhibited a cytotoxic profile similar to that of rilmenidine, but without appreciable affinity to α2 -adrenoceptors. In addition, compound5 significantly enhanced the apoptotic response to doxorubicin, and may thus represent an important tool for the development of better adjuvant chemotherapeutic strategies for doxorubicin-insensitive cancers.